The impact of multinational enterprises on community informal institutions and rural poverty - Brandl, Kristin; Moore, Elizabeth; Meyer, Camille; Doh, Jonathan (Journal of International Business Studies, 2022)
Multinational enterprise (MNE) investments in developing countries can induce a range of positive and negative impacts on host economies; the international business literature has tended to emphasize the former. Drawing from research on community informal institutions and institutional ecology, we explore the potential negative impacts of MNE investments on rural areas of developing countries. Specifically, we examine the impacts of foreign MNE land acquisitions for natural-resource-seeking purposes on the rural population by studying rural communities and their informal institutions. We find that land acquisitions by foreign MNEs weaken community informal institutions and, as a consequence, exacerbate rural poverty. Our research adds to the literature on the negative impact of MNE investments and provides additional perspectives on the role of informal institutions and institutional theory more broadly.